WORK PRODUCTIVITY OF TEACHERS OF SMP BATIK SURAKARTA IN 2021 - Sujoko Sujoko; Istiatin Istiatin; Sudarwati Sudarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to see the effect simultaneously or partially the variables of discipline, innovation ability, leadership style and emotional intelligence with teacher work productivity at SMP Batik Surakarta. Researchers conducted observations at SMP Batik Surakarta with the object of teacher research as a sample in order to determine the relationship between discipline, innovation ability, leadership style and emotional intelligence with teacher work productivity.The research method is in the form of survey research using quantitative research with a sample size of about 45 teachers. The data collection method used a questionnaire with a saturated sampling technique. Processing of data using the SPSS program using multiple regression equation analysis tools, F test, t test, and the coefficient of determination.The results of the analysis can be obtained that the variables of discipline, innovation ability, leadership style and emotional intelligence have a simultaneous effect on the teachers work productivity of SMP Batik Surakarta. Discipline has a significant effect on the teachers work productivity in SMP Batik Surakarta. Innovation ability has a significant effect on the teachers work productivity of SMP Batik Surakarta. Leadership style has a significant effect on the teachers work productivity of SMP Batik Surakarta. Emotional intelligence has a significant effect on the teachers work productivity at SMP Batik Surakarta. The results of the observation show that simultaneously the independent variables which include work motivation, job satisfaction and compensation have a relationship with teacher performance. Discipline, Innovation Ability, Leadership Style and Emotional Intelligence with Teacher Work Productivity